Evaluasi Galur-galur Padi Pup1 terhadap Cekaman Kekeringan - Wardoyo, Suwaji Handaru; Miftahudin, Miftahudin; Moeljopawiro, Sugiono; Prasetiyono, Joko (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
Drought, acidity, and P deficiency are problem in rice production in Ultisol soil in Indonesia. Pup1 locus in rice plant, besides has a role in uptaking P nutrient, was suspected to improve resistant to biotic and abiotic stresses, including drought. BC2F6 lines derived from Situ Bagendit cross containing Pup1 locus had been developed through Marker-assisted Backcrossing method, and had been tested for P fertilizers and resistance to blast. This research was aimed to evaluate the effect of Pup1 locus to drought stress condition. The study was divided into two experiments, namely test of polyethylene glycol (PEG) 8000 and test of root penetration ability test (DTA). The experiment was conducted at the Greenhouse of Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development, from November 2012 until May 2013. The number of lines used in this study was 52 lines, consisted of 24 lines of BC2F6 Situ Bagendit × Kasalath (= SK), 22 lines of Situ Bagendit × NIL-C433 (= SN), three parents namely Situ Bagendit (recurrent parent), Kasalath, and NIL-C433, two tolerant controls for drought namely Cabacu and Gajah Mungkur, and one sensitive control for drought IR20. The research used a completely randomized design for test PEG 8000 and a split-split plot design for test of root penetration ability. Results showed that maximum PEG 800 concentrations for drought stress study on rice was 20%. Pup1 locus was more tolerant to drought stress in PEG 8000 experiment through its longer roots and plumules. Pup1 locus gave a positive effect on root penetration ability, with longer roots and more penetrating wax layer. Pup1 locus also showed tolerant to drought on Ultisols soil, as indicated by an increasing dry weight of root and shoot than those of parent without Pup1 locus.